Institutional dynamics of Mopane woodland management in Bulilima district of Zimbabwe - SITHOLE, MKHOKHELI (Journal of Soil and Water Conservation, 2020)
The paper discusses the institutional dynamics influencing the management of Mopane woodlands in Bulilima district of Zimbabwe. The existence of Mopani woodlands as common pool resources in Bulilima makes them vulnerable to over-exploitation. The institutions responsible for sustainable management seem very weak. Common pool resources have been condemned as environmentally unsustainable, economically unviable or socially anachronistic especially when they become de facto open access resources. The dismantling of local institutions in Zimbabwe came with a complete disregard of indigenous knowledge. Independent Zimbabwe inherited policies that assumed ignorance among rural users. The policies currently in operation are fuzzy, inchoate, and falling between local traditional governance systems which in themselves are not clearly defined and state control which is so far removed from the day to day management of the resources. A question therefore arises on the implications of the current institutional dynamics on Mopani tree use and management. The study thus attempted to establish the institutional dynamics relating to Mopani tree use and management in Bulilima profile the implications of such changes in the use behaviour of users and managers and establish the existing potential within the existing institutions for management of Mopani trees. As a way of gathering data this study is largely ethnographic, involving different approaches that allow for close attention such as observations, participation in the observed practices and events, in-depth interviews, narratives and archival research. Questionnaires have also been used to augment qualitative data. Findings indicate that at community level, there are a multiplicity of institutions and management structures with unclear mandates and jurisdictions. Power and knowledge dynamics influence processes of negotiating resource access by various actors. Although women have historically been sidelined in formal decision-making processes, they seem to be playing a key role in Bulilima largely because men are in Botswana and South Africa.